PENGARUH TABATA WORKOUT TERHADAP KEBUGARAN JASMANI PESERTA DIDIK YANG MENGGUNAKAN DUAL SYSTEM DI SMK SMTI PONTIANAK - Mubarok, Rizki; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe problem in this study is the lack of physical fitness of students when implementing a dual system which is a program from schools that requires students to do learning outside of school or an internship, where there is no physical education learning or physical activity provided to students so that the physical fitness of participants students decline. The aim of the research is to find out whether there is an influence of the workout tabata on physical fitness in students who use dual systems at SMK SMTI Pontianak.The method used in this study is an experiment with a form of research Pre-Experimental Design, One-Group Pretest-Posttest Design. The subjects in this study were students of class XI who applied a dual system of 46 people at the SMK SMTI Pontianak. Data analysis with t-test. From the results of statistical calculations, t count 2.46> t table 1.98 with a significant level of 0.05, it can be concluded that there is a significant effect of tabata training on physical fitness of students.Keywords: Fitness , Physical Tabata Workout.